2014
DOI: 10.1111/ina.12114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ultrafine particles in Portuguese preschools: levels and exposure doses

Abstract: The aim of this work was to assess ultrafine particles (UFP) number concentrations in different microenvironments of Portuguese preschools and to estimate the respective exposure doses of UFP for 3-5-year-old children (in comparison with adults). UFP were sampled both indoors and outdoors in two urban (US1, US2) and one rural (RS1) preschool located in north of Portugal for 31 days. Total levels of indoor UFP were significantly higher at the urban preschools (mean of 1.82 9 10 4 and 1.32 9 10 4 particles/cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 43 publications
4
60
0
Order By: Relevance
“…Only one Portuguese study was found (Fonseca et al, 2014) that sampled UFP number concentrations, in three preschools. Despite the different type of education institution (preschools vs. primary schools) the obtained levels of UFP were in general similar to those of the current investigation (7.14x10 3 to 1.13x10 4 pt/cm 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one Portuguese study was found (Fonseca et al, 2014) that sampled UFP number concentrations, in three preschools. Despite the different type of education institution (preschools vs. primary schools) the obtained levels of UFP were in general similar to those of the current investigation (7.14x10 3 to 1.13x10 4 pt/cm 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two portable condensation particle counters (P-Trak model 8525, TSI, Inc., Shoreview, MN) were used for measurement of UFP number concentrations. The operation mechanism of these particle counters is based on the principle of condensing 100% grade isopropyl alcohol (Sigma-Aldrich, Steinheim, Germany) onto UFP in order to increase their dimensions to detectable sizes (Fonseca et al, 2014). The particle detection limit ranged from 0.02 to larger than 1 µm.…”
Section: Indoor and Outdoor Air Samplingmentioning
confidence: 99%
“…This is especially true for specific risk groups such as children. The early school years are considered as a long period of vulnerability given that susceptibility to environmental threats is elevated (Fonseca et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been some concern regarding the topic, which may be epitomized by several published studies (Buonanno et al 2013a, Buonanno et al 2013b, Cavaleiro Rufo et al 2015, Diapouli et al 2008, Fromme et al 2007, Morawska et al 2009, there are no studies assessing children exposure to UFPs in urban and rural primary schools in Portugal. However, Fonseca et al (2014) recently published a study concerning pre-school children exposure to UFPs in two urban and one rural pre-schools, where it was not only shown that children in urban pre-schools are more exposed to UFP pollution than children in rural schools, but they are also four to six times more exposed than adults with similar daily schedules. Since primary schoolchildren spend more time in school than pre-schoolchildren, with longer lecture periods, it is possible that the exposure to indoor UFPs is also higher.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, besides one study by the authors focusing on PM assessment (Branco et al, 2014a) and another focusing on the levels of ultrafine particles in Portuguese preschools (Fonseca et al, 2014), there is only one study on IAQ in Portuguese day care centres (Carreiro-Martins et al, 2014) which assessed indoor CO2 concentrations (as a ventilation surrogate marker) and comfort parameters, relating them to wheezing in attending children. Despite the considerable number of buildings and the three classrooms per building analysed, Carreiro-Martins et al…”
Section: Introductionmentioning
confidence: 99%